Fungsi Mitos Di Desa Karangjati Kecamatan Tarub Kabupaten Tegal - Nurkhayatun, Umi; Werdiningsih, Yuli Kurniati (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2025)
This study used descriptive qualitative method. Descriptive is describing and describing the function of myth, while qualitative is a method that uses words, phrases, clauses, and sentences as data. The purpose of this study was to determine the function of the myths that exist in Karangjati Village, Tarub District, Tegal Regency. Myths are anonymous stories or unknown creators who come from primitive cultures. These stories are sacred and cannot be understood scientifically. This myth is one of the oral culture that still exists in society and is part of oral folklore. Oral folklore is passed down from generation to generation orally or by word of mouth. Data collection techniques used in this research are observation, interview, record and note. Observation technique is the observation of the situation and research location. Then, the interview is asking or talking directly to existing sources about the myths at the research site and then recorded using a tape recorder and then taking notes according to the results of interviews and recordings. The results obtained from this study are that there are several myths that exist in Karangjati Village, Tarub District, Tegal Regency, including myths about pregnancy, myths about small children and myths about marriage or matchmaking. The functions of these myths include; (1) as a means of education; (2) as a means of entertainment; (3) as a means of culture; and (4) as a means of reminder.